Near-Infrared-II Nanoparticles for Cancer Imaging of Immune Checkpoint Programmed Death-Ligand 1 and Photodynamic/Immune Therapy - Liu, Qiang; Tian, Jiangwei; Tian, Ye; Sun, Qinchao; Sun, Dan; Wang, Feifei; Xu, Haijun; Ying, Guoliang; Wang, Jigang; Yetisen, Ali K; Jiang, Nan (ACS nano, 2021)
Development of second near-infrared (NIR-II) nanoparticles (NPs) with high biocompatibility, low toxicity, and high singlet oxygen quantum yield (ΦΔ) to prevent tumor recurrence is highly desirable in molecular imaging and photodynamic/immune combination therapy. Here, theranostic photosensitizer BODIPY (BDP)-I-N-anti-PD-L1 NPs were developed by encapsulating the photosensitizer BDP-I-N with amphipathic poly(styrene-co-chloromethylstyrene)-graft-poly(ethylene glycol) nanocarriers through self-assembly functionalization with programmed cell death-ligand 1 (PD-L1) monoclonal antibody. These NPs exhibit highly intensive luminescence in the NIR-II window (1000–1700 nm) to real-time imaging of immune checkpoint PD-L1, high singlet oxygen quantum yield (ΦΔ = 73%), and an eliminating effect of primary cancers. The NPs also allow for profiling PD-L1 expression as well as accumulating in MC38 tumor and enabling molecular imaging in vivo. Upon an 808 nm laser excitation, the targeted NPs produce an emission wavelength above 1200 nm to image a tumor to a normal tissue signal ratio (T/NT) at an approximate value of 14.1. Moreover, the MC38 tumors in mice are eliminated by combining photodynamic therapy and immunotherapy within 30 days, with no tumor recurrence within a period of 40 days. In addition, the tumors do not grow in the rechallenged mice within 7 days of inoculation. Such a strategy shows a durable immune memory effect against tumor rechallenging without toxic side effects to major organs.